Mahātmā Gāndhī kā viśvavyāpī prabhāva - Ṭhākura, Keśava Kumāra (SAMP early 20th-century Indian books project ;, 1930)
On Mahatma Gandhi, 1869-1948, statesman with special reference to his influence in the world.